2000
DOI: 10.1111/0824-7935.00119
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in Human Nonmonotonic Reasoning

Abstract: Although humans seem adept at drawing nonmonotonic conclusions, the nonmonotonic reasoning systems that researchers develop are complex and do not function with such ease. This paper explores people's reasoning processes in nonmonotonic problems. To avoid the problem of people's conclusions being based on knowledge rather than on some reasoning process, we developed a scenario about life on another planet. Problems were chosen to allow the systematic study of people's understanding of strict and nonstrict rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 7 publications
0
36
0
Order By: Relevance
“…Hewson and Vogel (1994;Vogel, 1996) found that most people were reluctant to come to any conclusion for the problems they gave. Ford and Billington (2000) showed that when conclusions could not be retrieved from background knowledge, subjects did not overwhelmingly give the expected answers based on the specificity principle. Thus, for example, in two different studies, only 7 out of 19 and 2 out of 12 subjects drawn from a student population gave the expected, negative, answer to problems with the structure of (1).…”
Section: Is Stordy Found On Cliffs?mentioning
confidence: 99%
See 3 more Smart Citations
“…Hewson and Vogel (1994;Vogel, 1996) found that most people were reluctant to come to any conclusion for the problems they gave. Ford and Billington (2000) showed that when conclusions could not be retrieved from background knowledge, subjects did not overwhelmingly give the expected answers based on the specificity principle. Thus, for example, in two different studies, only 7 out of 19 and 2 out of 12 subjects drawn from a student population gave the expected, negative, answer to problems with the structure of (1).…”
Section: Is Stordy Found On Cliffs?mentioning
confidence: 99%
“…Thus, for example, given all echidnas are mammals, mammals usually do not lay eggs, Susie is an echidna, we can assume (erroneously in fact) that echidnas do not lay eggs and that Susie does not lay eggs, until we hear otherwise. Ford and Billington (2000) gave 19 university students a series of problems like (3) and (4) (though without the diagrammatic representations) where the content was about fictitious plants and animals and where conclusions could therefore not be simply retrieved from memory. For (3), all 19 subjects concluded that Garffi was likely to be found in deserts; for (4), 17 concluded Stordy was likely to be found on cliffs.…”
Section: Is Stordy Found On Cliffs?mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the long tradition of psychological experiments on classical logics and syllogistics (Rips, 2002(Rips, , 1994JohnsonLaird, 1999;Johnson-Laird & Byrne, 1994;Bacon et al, 2003;Newstead, 2003;Morley et al, 2004), only a few studies, though, have investigated nonmonotonic reasoning empirically (Benferhat et al, in press;Da Silva Neves et al, 2002;Ford & Billington, 2000;Ford, in press, 2004Ford, in press, , 2005Pfeifer, 2002;Pfeifer & Kleiter, 2003, in press;Pelletier & Elio, 2003;Schurz, in press). …”
Section: Problem 2: Monotonicitymentioning
confidence: 99%